STRATEGIC ANALYSIS OF INCREASE OF INCOME THROUGH MARKET SHARE EXPLANATION WITH QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) APPROACH (Study in Lampung Telecommunication Business Area) - Sajidah AZ, Selma Jilan; suripto, Suripto (Jurnal Kompetitif Bisnis, 2022)
This study aims to analyze the strategy of increasing revenue for the Lampung Telecommunication Business Area through market expansion with the Quantitative Strategic Planning Matrix in the Lampung Telecommunication Business Area. Consists of 3 research informants, which is a descriptive study with a qualitative approach. Quantitative strategic planning matrix (QSPM) stages 1. The input stage is the internal strategic factors analysis summary (IFAS) matrix with a weight score of 3.0 and the external strategic factors analysis summary (EFAS) matrix with a weighted score of 3.3. The next step. 2. The analysis stage is the SWOT analysis matrix which results in the Lampung Telecommunication Business Area being in quadrant 1 position which is supporting aggressive strategy, and for the internal external matrix (IE) it is in cell I which is growing and building and the decision stage is the quantitative strategic planning matrix which produces market penetration strategy, market development strategy and product development, for other alternative strategies, namely sales agents remain selective to consumers by implementing 5C in order to increase revenue by expanding market share in the Lampung Telecommunication Business Area.